ANALISIS KEMAMPUAN MENULIS TEKS DESKRIPSI PESERTA DIDIK KELAS III B SD XAVERIUS 3 PALEMBANG - Lusia Claudia Febiyanti (Universitas Katolik Musi Charitas, 2023)
The background of this study was to determine the ability to write descriptive texts of third grade students at SD Xaverius 3 Palembang. The purpose of the study was to determine the ability to write descriptive texts of third grade students at SD Xaverius 3 Palembang. This research is entitled